Threats to liberty in Germany - Chai, J (Refugee Studies Centre, University of Oxford, 2013)
Those seeking asylum in Germany face fast-track assessments, risk of immediate detention and deportation, and lengthy stays in ‘communal shelters’ scattered throughout Germany.